Risk factors associated with in-hospital mortality during yellow fever outbreak in Brazil - McClure, Max; Rezende, Izabela Maurício de; Pereira, Leonardo Soares; Dutra, Maria Rita Teixeira; Fradico, Jordana Rodrigues Barbosa; Macedo, Rodrigo; Marçal, Marcelle Cardoso; Fonte Boa, Lívia Soares Coelho; Bragato, Alexandre Maurício Castro; Faria, Flávio Augusto de Almeida; Pamplona, Livia; Said, Rodrigo Fabiano do Carmo; et al. (Frontiers in Medicine, 2025)
ObjectiveTo characterize the clinical manifestations of yellow fever disease and identify risk factors for mortality.MethodsA retrospective study was conducted in the referral center for infectious diseases (Hospital Eduardo de Menezes-HEM) in Belo Horizonte, Minas Gerais, Brazil. Analysis included data from 283 patients with confirmed YF infection older than 13 years old who presented to HEM between January 2017 and June 2018. In-hospital mortality (hypothesis formulated after data collection), demographic factors and clinical and laboratory assessments were used.ResultsStudy patients were mainly men (87.6%), with a median age of 46.0 (IQR 36.5, 57.0). 131 (46.3%) patients were admitted to the ICU, and 62 (22.0%) used invasive mechanical ventilation for a median of 2 days (IQR 1, 3). The median (IQR) total length of stay (LOS) in the ICU was 6 days (IQR 4, 8). The in-hospital mortality rate was 24.0%. Age was significantly higher in fatal (median 49.5, IQR 41.0, 61.0]) than in non-fatal cases [46 (36, 55)] (p < 0.01). Male sex was associated with an increased risk of death (RR 4.66, 95% CI 1.19, 18.2; p < 0.01). Most common symptoms and signs on admission to HEM were fever (31.9%), myalgia (27.8%), jaundice (24.3%), headache (23.9%), abdominal pain (16.1%), vomiting (12.2%), weakness (10.4%), and arthralgias (10.0%). Initial viral load above the cutoff of 4.45 log10 copies/mL was significantly associated with death prior to discharge (OR 12.2; CI 2.83, 92.3). Five factors were significantly related to increased odds of death prior to discharge: log-transformed AST (OR 3.65; CI 2.02, 7.81; p < 0.001), log-transformed INR (OR 7.40; CI 1.31, 33.0; p = 0.010), log-transformed lactate (OR 4.57; CI 1.48, 17.1; p = 0.013), log-transformed WBC (OR 4.33; CI 1.19, 18.5; p = 0.034), and age (OR 1.06; CI 1.01, 1.12; p = 0.026).Conclusions and relevanceAST, INR, lactate, WBC, and age are statistically associated with death prior to discharge in YF patients. These clinical markers should be applied to improve patient screening and management during future YF epidemics.